A Comparison of Individual Bored Pile Bearing Capacity Using the Results of Standard Penetration Test (SPT) and Pile Driving Analysis (PDA) Test of the Railway Bridge Foundation - Ayu Prativi; Puspita Dewi; Nila Sutra; Wahyu Tamtomo Adi; Chi Weijia (Journal of Railway Transportation and Technology, 2022)
Prediction of the bearing capacity of deep foundations using analytical methods from the results of the standard Penetration Test has been carried out until now due to practical consideration. However, with the many types of empirical formulas proposed by various researchers, it is necessary to test the validity of the values predicted by the empirical formulas. During the construction stage, the bearing capacity of deep foundations can be checked using the Pile Driving Analysis (PDA) Test. This study aimed to compare the foundation bearing capacity prediction results using analytical methods of Luciano Decourt (1982), Reese and O'Neil (1999), and Building Standard Law of Japan with the results from PDA test. The comparison indicate that the analytical method of Luciano Decourt (1982) predict bearing capacity with the smallest error rate, which is 1.97% to 38.99% with safaty factor (SF) 2 to 3 on a relatively homogeneous and heterogeneous soil conditions. Prediction of bearing capacity of bored pile foundations using analytical methods O'Neil & Reese (1999) and Building Standard Law of Japan provide better performance for soil types which is dominated by cohesive soils with safety factor (SF) 2.